U progu przełomu politycznego w obradach Sejmu Wielkiego w początkach drugiej połowy roku 1790 - Szczygielski, Wojciech (Przegląd Nauk Historycznych, 2014)
In 1790 there was a political breakthrough in the debates of the Great Seym. It was marked by: a crisis of social trust in the Potocki family, the gentry’s support for the king, taking over the initiative to draft the constitution by Stanisław August. From the very beginning of 1790 the Potocki family were more and more often accused of oligarchic tendencies and an attempt to seize the control of the country for their own benefit. On the other hand, joining the Polish-Prussian alliance by Stanisław August (March 1790) made the king more and more popular both in the Seym and in the provinces. The king, having definitely rejected the pro-Russian orientation, started to be perceived by the landed gentry as a much more reliable advocate for the democracy of the gentry than the Puławy party. A special role in the breakthrough mentioned above and in taking over the con- stitutional initiative by the king was played by the elite of the gentry who wanted to shape the Commonwealth following the model of the leading free states of the contemporary world. The article looks at the parliamentary sessions that were held in August 1790. It is during these sessions that for the first time the gentry presented, as strongly as never before, their critical attitude towards the Potocki family showing at the same time their support for the king. The August parliamentary sessions became the announcement of the political breakthrough in the seym debates which was about to happen. This breakthrough came in the first half of September 1790 when Stanisław August received the right of nomination for the highest offices, contrary to the initial intention of Ignacy Potocki (session from 13th September 1790).